Drivers of social media adoption among SMEs amidst the COVID-19 pandemic / Lina Nadia Abd Rahim, Nur Atiqah Zakiyyah Ramlee and Lennora Putit - Abd Rahim, Lina Nadia; Ramlee, Nur Atiqah Zakiyyah; Putit, Lennora (Universiti Teknologi MARA, Selangor, 2022)
This study attempts to provide a comprehensive view of previous literature on social media adoption. The COVID- 19 outbreak has indirectly influenced social media usage in various events as a tool of marketing and communication platform among SMEs. Hence, social media adoption study is important in encouraging the business growth and productivity. This literature review study covers empirical studies that has been conducted on the factors affecting social media adoption in various contexts. For the literature review, meta-analysis is used to find, choose, evaluate, and combine data pertinent to the factors influencing the adoption of social media.